PENGARUH MODEL PEMBELAJARAN TEAM GAME TOURNAMENT TERHADAP KEMAMPUAN BERPIKIR KRITIS ILMU PENGETAHUAN SOSIAL SISWA KELAS V SD NEGERI 43 PALEMBANG - Denny Deslanda Putra Mukti; Destiniar; Eka Fitri Puspa Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background in this study is the low ability to think critically in Social Science subjects of fifth grade students of SD Negeri 43 Palembang. This study aims to determine the effect of the Team Game Tournament learning model on the critical thinking ability of social science fifth grade students of SD Negeri 43 Palembang. This research is a quantitative research with experimental method (Quasi Experimental Design) with Posttest-Only design. The data collection technique in this study was a test instrument in the form of a posttest question. The sample in this study used saturated sampling, namely 37 students of SD Negeri 43 Palembang. The results showed that based on the t-test, the tcount value was 3.484 and the ttable was 2.030, meaning that the t count> t table, Ha was accepted and Ho was rejected. So it can be concluded that the Team Game Tournament learning model in social science subjects has a significant influence on the critical thinking skills of social science class V students of SD Negeri 43 Palembang